Wisdom literature - Balentine, Samuel E. 1950- (Nashville, TN Abingdon Press, 2018)
Cover; Half title; Title; Copyright; Dedication; Contents; General Preface; Abbreviations; Introduction: Wisdom and wisdom; Chapter 1: Proverbs: "Wisdom Begins with the Fear of the Lord"; Composition History; Literary Forms; Sociopolitical Context; Thematic Coherence; Chapter 2: Job: "Wisdom, Where Can It Be Found?"; Form, Structure, and Genre; A Man Named Job; For No Reason; Ultimate Questions, Penultimate Answers; Wisdom, Where Can It Be Found? Where Is the Place of Understanding?; Epilogue or Eulogy?; Chapter 3: Ecclesiastes: "Perfectly Pointless"; Authorship, Date, and Structure.
Rhetorical Strategy Qohelet's Intellectual World; The End of the Matter; Chapter 4: Sirach: "All Wisdom Involves Doing the Law"; Form, Structure, and Rhetorical Strategy; Ethos and Ethics; Fear of God, Wisdom, and Law: The Ethics of Submission; Ben Sira's God: "The Lord Is the All"; Chapter 5: Wisdom of Solomon: "Doing What Is Right Means Living Forever"; Historical and Cultural Contexts; Intellectual Economy; Key Issues and Theological Themes; Conclusion: The End of Wisdom; Notes.
Wisdom literature is foundational to our life and learning
Includes bibliographical references
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible; Wisdom Literature -- Criticism, interpretation, etc; RELIGION ; Biblical Studies ; Old Testament; RELIGION ; Biblical Studies ; Wisdom Literature; Wisdom Literature; Criticism, interpretation, etc; Electronic books